A two-dimensional graphitized nanocarbon material and its preparation method and electrochemical application
By preparing two-dimensional graphitized nanocarbon materials with high graphitization, the problem of low efficiency of carbon material electrodes in the prior art in energy storage and conversion applications is solved, and supercapacitor electrode materials with high specific capacitance and cyclic stability are achieved .
Patent Information
- Application Number
- CN202111466011.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-12-03
AI Technical Summary
It is difficult for the prior art to effectively build high-efficiency carbon material electrodes that meet energy storage and conversion needs. Although biomass carbon materials have broad development prospects, their application in fields such as supercapacitors still has challenges.
Using a two-dimensional graphitized nanocarbon material and its preparation method, graphitized nanometers with porous sheet structure and high specific surface area are obtained by acid-base treatment, enzymatic decomposition, metal catalyst mixing and high temperature carbonization treatment. Carbon materials and increase their graphitization degree through chemical alkali activation treatment.
The high specific capacitance and cycle stability of graphitized nanocarbon materials in supercapacitor electrodes were achieved. The modified foam nickel electrode had a specific capacitance of 448 F g-1 at 1 A g-1 current density, and the capacity was maintained after 5000 cycles. The rate is as high as 94.92%~98.46%, and it shows low AC impedance.
Smart Images

Figure CN114334469B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials and relates to a two-dimensional graphitized nano-carbon material and a preparation method and electrochemical application thereof. Background Art
[0002] In recent decades, the conversion of low-value biomass into high-quality, high-energy-density, clean, zero-CO2 emission materials with commercial value has become a research hotspot. As a natural organic polymer, biomass has a high carbon content, wide availability, low cost, and renewable resources, and has broad development prospects. Therefore, they are often used as carbon precursors to construct biocarbon materials, which are widely used in supercapacitors, electrocatalysis, electrochemical sensors, and lithium / sodium ion batteries. In recent years, people have conducted extensive research on the conversion of natural biomass into various functional carbon materials. The heteroatoms and large surface area in the carbon skeleton are conducive to ion diffusion and accelerated electron transfer reactions, which are important factors affecting its application in energy storage and conversion. Although biomass carbon material electrodes have broad development prospects, it is still a huge challenge to rationally and efficiently construct carbon material electrodes that meet the needs of energy storage and conversion. Summary of the invention
[0003] In view of this, the present invention provides a two-dimensional graphitized nano-carbon material and a preparation method and application thereof. The preparation method of the graphitized nano-carbon material provided by the present invention is simple, easy to operate, and has high yield. When used as a supercapacitor electrode material, it has extremely high specific capacitance and cycle stability.
[0004] The invention provides a graphitized nano-carbon material, wherein the graphitized nano-carbon material has a porous structure; the graphitized nano-carbon material has a sheet structure.
[0005] Preferably, the specific surface area of the graphitized nanocarbon is 900-1300 m 2 g -1 .
[0006] Preferably, the graphitized nanocarbon has a thin flat lamellar structure.
[0007] The present invention provides a method for preparing the graphitized nano-carbon material described in the above technical solution, comprising the following steps: (1) soaking the biomass fish scales in strong acid and strong alkali solutions in sequence, then cleaning with ultrapure water, draining the water, adding a quantitative bioenzyme and ultrapure water, stirring and reacting for 24 hours, and filtering to obtain a liquid solution; (2) mixing the solution prepared in step 1 with a certain amount of metal catalyst at 40-50°C, stirring evenly, and then vacuum drying for 2-24 hours to obtain a solid substance; (3) heating at 4-12°C min -1The temperature was raised to 800-1000°C at a rate of 80-120 ml min -1 (4) subjecting the product obtained in step 3 to acid treatment to remove the metal substances therein and obtaining a black solid; (5) subjecting the product obtained in step 4 to chemical alkali activation treatment to obtain a graphitized nanocarbon material.
[0008] Preferably, the molar concentration of the strong base solution is preferably 1 to 20 mol L -1 , the strong alkaline solution is potassium hydroxide solution and / or sodium hydroxide solution; the concentration of the strong acid is 10-40%, and the strong acid is concentrated hydrochloric acid; the mass concentration of the enzyme is 10-40%, and the enzyme is alkaline protease.
[0009] Preferably, the mass ratio of the catalyst to the biomass precursor is 1:(1-3); the catalyst is potassium ferrocyanide, potassium ferrocyanide, ferric chloride, ferric nitrate or ferric sulfate.
[0010] Preferably, the carbonization temperature is 800-1000 °C, the time is 2-4 h, and the heating rate to the carbonization temperature is 4-12 °C min -1 .
[0011] The present invention provides the use of the two-dimensional graphitized nano-carbon material described in the above technical solution or the two-dimensional graphitized nano-carbon material obtained by the preparation method described in the above technical solution in supercapacitor electrode materials.
[0012] The graphitized nano-carbon material provided by the present invention is a porous lamellar structure, composed of a porous two-dimensional carbon film, with a large specific surface area, a high degree of graphitization, and nitrogen doping, which is beneficial to improve the specific capacitance of the material when it is actually used. The results of the examples show that the foamed nickel electrode modified with the graphitized nano-carbon material provided by the present invention has a specific capacitance of 1 A g -1 The optimal specific capacitance at the current density is 448 F g -1 1A g -1 After 5000 cycles at a current density of , the capacity retention rate of the electrode is 94.92~98.46%, and the AC impedance test results show that its charge transfer resistance is 0.15~0.34 Ω. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is a transmission electron microscope image of the graphitized nanocarbon material prepared in Example 1.
[0014] Figure 2 This is the X-ray diffraction spectrum of the graphitized nanocarbon material prepared in Example 1.
[0015] Figure 3This is the X-ray photoelectron spectrum of the graphitized nanocarbon material prepared in Example 1.
[0016] Figure 4 This is the XPS spectrum of the core energy level region of C1s in the graphitized nano-carbon material prepared in Example 1.
[0017] Figure 5 This is the XPS spectrum of the core energy level region of O1s in the graphitized nano-carbon material prepared in Example 1.
[0018] Figure 6 This is the XPS spectrum of the core energy level region of N1s in the graphitized nano-carbon material prepared in Example 1.
[0019] Figure 7 This is the adsorption isotherm curve of graphitized nanocarbon material in Application Example 1.
[0020] Figure 8 This is the pore size distribution curve of the graphitized nanocarbon material in Application Example 1.
[0021] Fig. 9 This is a cyclic voltammetry curve of the graphitized nanocarbon material / nickel foam supercapacitor electrode scanned as the working electrode in Application Example 1.
[0022] Fig.10 This is a constant current charge and discharge curve diagram of Application Example 1 using graphitized nano-carbon material / nickel foam supercapacitor electrode as a working electrode.
[0023] Fig.11 This is the Nyquist curve diagram of Application Example 1 when the graphitized nano-carbon material / nickel foam supercapacitor electrode is used as the working electrode.
[0024] Fig.12 This is a test diagram of the cycle stability of graphitized nanocarbon material / nickel foam supercapacitor electrode in Application Example 1.
[0025] Fig.13 This is a cyclic voltammetry curve of the graphitized nanocarbon material / nickel foam supercapacitor electrode scanned as the working electrode in Application Example 2.
[0026] Fig.14 This is a constant current charge and discharge curve diagram of Application Example 2 where the graphitized nano-carbon material / nickel foam supercapacitor electrode is used as the working electrode.
[0027] Fig.15 This is the Nyquist curve diagram of Application Example 2 when the graphitized nano-carbon material / nickel foam supercapacitor electrode is used as the working electrode. DETAILED DESCRIPTION
[0028] The present invention provides a two-dimensional graphitized nano-carbon material, a preparation method thereof and electrochemical applications. The preparation method of the graphitized nano-carbon material provided by the present invention is simple, easy to operate and has high yield. When used as a supercapacitor electrode material, it has extremely high specific capacitance and cycle stability.
[0029] The graphitized nanocarbon provided by the present invention has a specific surface area of 900-1300 m 2 g -1 .
[0030] Preferably, the graphitized nanocarbon has a thinner lamellar structure.
[0031] In the present invention, the method for preparing the graphitized nano-carbon material preferably comprises the following steps: firstly, the biomass raw material is treated with acid and alkali in sequence, and then enzymatically hydrolyzed to obtain liquefied biomass.
[0032] In the present invention, the biomass raw material is preferably fish scales; the present invention preferably pre-treats the biomass raw material. In the present invention, the pre-treatment preferably includes: washing, drying, acid treatment, alkali treatment and enzymolysis of the biomass raw material in sequence. In the present invention, the washing is preferably water washing, and the present invention has no special requirements for the specific implementation process of the drying.
[0033] In the present invention, the alkali treatment is preferably potassium hydroxide solution and / or sodium hydroxide solution, and the molar concentration of the strong alkali solution is preferably 1 to 20 mol L -1 , more preferably 5 to 10% mol L -1 .
[0034] In the present invention, the strong acid solution is preferably concentrated hydrochloric acid, and the mass concentration of the strong acid is preferably 10-40%, more preferably 20-30%.
[0035] In the present invention, the volume ratio of the wet weight of the biomass raw material to the strong alkaline solution or the strong acid solution is preferably (40-50) g: (240-300) mL.
[0036] In the present invention, the biological enzyme is preferably an alkaline protease solution, preferably with a mass concentration of 10% to 40%, more preferably 25% to 35%.
[0037] The present invention has no special requirements for the specific implementation process of mixing the biomass raw material and the strong alkali or strong acid solution. In the present invention, the time of the acid treatment and the alkali treatment is preferably 12 to 24 hours, and the temperature of the acid treatment and the alkali treatment is preferably room temperature.
[0038] In the present invention, the enzymatic hydrolysis time is preferably 24 h, and the enzymatic hydrolysis temperature is preferably 50-80° C., more preferably 65-75° C.
[0039] The present invention preferably performs post-treatment on the system obtained by enzymatic hydrolysis to obtain enzymatic biomass. In the present invention, the post-treatment preferably includes: sequentially performing solid-liquid separation and concentrating and refrigerating. In the present invention, the solid-liquid separation is preferably filtration. The present invention preferably concentrates and refrigerates the solid product after solid-liquid separation for standby use; in the present invention, the concentration is preferably evaporative concentration, and the concentration temperature is preferably 50-60°C; the present invention has no special requirements for the evaporation time to achieve the concentration of the liquid to 30% of the original volume; in the present invention, the refrigeration is household refrigerator refrigeration, and there is no special requirement for the refrigeration time, and the refrigeration temperature is preferably 1-4°C.
[0040] After obtaining the enzymatically hydrolyzed biomass, the present invention adds a metal catalyst to the enzymatically hydrolyzed biomass under a protective atmosphere, performs high-temperature carbonization, and obtains a black solid substance; the obtained solid substance is then ground, treated with a strong acid, and then washed with ultrapure water and ethanol, and dried to obtain a graphitized nano-carbon material, thereby obtaining a porous two-dimensional carbon material having the characteristics of a large specific surface area and a high degree of graphitization.
[0041] In the present invention, the metal catalyst includes potassium ferrocyanide, potassium ferrocyanide, ferric chloride, ferric nitrate or ferric sulfate, the carbonization temperature is preferably 800-1000 ° C, the carbonization time is 2-4 h, and the heating rate to the carbonization temperature is preferably 4-12 ° C / min, more preferably 8-10 ° C / min; in the present invention, the protective gas is preferably any one of nitrogen and argon, more preferably nitrogen. The flow rate of the protective atmosphere is preferably 80-120 mL / min, more preferably 100-115 mL / min.
[0042] The present invention preferably performs post-treatment on the solid product obtained after carbonization. In the present invention, the post-treatment preferably includes strong acid treatment, the strong acid is preferably concentrated hydrochloric acid, and the concentrated hydrochloric acid preferably has a concentration of 10-40%, more preferably 20-30%; the washing is preferably water washing, and the present invention has no special requirements on the number of washings, as long as the solid product is washed to neutrality.
[0043] In the present invention, the supercapacitor electrode material preferably includes the following components in parts by mass:
[0044] 70-90 parts of graphitized nano-carbon material; 5-20 parts of conductive agent; 5-15 parts of binder;
[0045] In terms of mass fraction, the supercapacitor electrode material provided by the present invention comprises 70 to 90 parts of graphitized nano-carbon material, preferably 85 parts. In the present invention, the graphitized nano-carbon material is the graphitized nano-carbon material [ryy1] described in the above technical solution.
[0046] Based on the graphitized nano-carbon material, the supercapacitor electrode material provided by the present invention includes 5 to 20 parts of a conductive agent, preferably 10 parts. In the present invention, the conductive agent preferably includes acetylene black and / or carbon black Super-p.
[0047] Based on the graphitized nano-carbon material, the supercapacitor electrode material provided by the present invention includes 5 to 20 parts of a binder, preferably 5 parts. In the present invention, the binder is preferably polyvinylidene fluoride and / or polytetrafluoroethylene.
[0048] The present invention provides a method for preparing a supercapacitor electrode from the supercapacitor electrode material described in the above technical solution, comprising the following steps.
[0049] The graphitized nano-carbon material, the conductive agent, the adhesive and the polar organic solvent are mixed to obtain an electrode slurry; the electrode slurry is scraped onto a conductive substrate, dried and pressed into sheets to obtain a supercapacitor electrode.
[0050] In the present invention, the polar organic solvent is preferably N-methyl-2-pyrrolidone. The present invention has no special requirements on the amount of the polar organic solvent; the present invention has no special requirements on the specific implementation process of the mixing, as long as the materials are mixed evenly.
[0051] After obtaining the electrode slurry, the present invention preferably scrapes the electrode slurry on the surface of the conductive substrate and then dries and presses it to obtain a supercapacitor electrode. In the present invention, the conductive substrate is preferably nickel foam, and the size of the conductive substrate is preferably 1cm×1cm; the present invention has no special requirements for the thickness of the scraping and the specific implementation process of the coating, and the conventional scraping thickness and operation well known to those skilled in the art can be used; in the present invention, the drying temperature is preferably 50~90℃, more preferably 60~75℃; the drying time is preferably 12~24h, more preferably 12h; in the present invention, the pressure of the tablet is preferably 10MPa; the present invention has no special requirements for the specific implementation process of the stamping.
[0052] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0053] Example 1
[0054] First, the fish scales were decomposed to extract the hydrolyzate. The specific steps are as follows: First, the fish scales were treated with 30% concentrated hydrochloric acid and 10 molL -1Soak in NaOH for 24 h respectively, then wash with water until neutral and drain naturally. Then accurately weigh 12.5 g of pretreated fish scales and add 250 ml of alkaline protease solution. Stir the above mixture at 75 °C for 12 h until the fish scales are completely decomposed, and then filter with filter membranes with pore sizes of 0.45 μm and 0.22 μm in turn. The filtrate is heated and stirred at 75 °C for 4 h to obtain a uniformly concentrated carbon precursor solution, which is stored in a refrigerator at 4 °C for further use. Take 30 ml of the precursor solution, add 0.02 mol potassium ferrocyanide, and stir for 1 hour to form an orange transparent solution; transfer this solution to a corundum boat and dry it at 80 °C to obtain a green solid substance, which is then placed in a tube furnace and heated to 900 °C at a heating rate of 5 °C / min for carbonization for 3 hours to obtain a black solid substance. After grinding, the black solid material was added with an appropriate amount of concentrated hydrochloric acid and soaked for 12 h, then washed with ethanol and water until neutral, centrifuged, and dried at 80 °C to obtain graphitized nanocarbon material.
[0055] Figure 1 Transmission electron microscopy characterization of the prepared graphitized carbon material, where Figure 1 (a) is a transmission electron microscope photo with a scale of 1 μm. Figure 1 (b) is a transmission electron microscope image with a scale of 100 nm; Figure 1 It can be concluded that the graphitized carbon material prepared in this embodiment is a flat thin sheet structure.
[0056] Figure 2 The X-ray diffraction spectrum of the prepared graphitized nanocarbon material is Figure 2 Peaks at 26.4°, 42.2°, 44.5°, 54.5°, 59.7° and 77.4° can be clearly seen, which are diffraction peaks belonging to the (002), (100), (101), (004), (103) and (110) crystal planes of graphitized carbon. Figure 3 X-ray photoelectron spectrum of graphitized nanocarbon materials prepared from Figure 3 It can be determined that the main constituent elements of the material are carbon, nitrogen and oxygen.
[0057] Figure 4 The XPS spectrum of the C1s core level region in the prepared graphitized nanocarbon material is shown in Figure 2. Figure 4 Four split peaks are shown at 284.7 eV~285.6 eV, 288.7 eV and 289.6 eV, corresponding to the binding energies of sp2 C and sp3 C, CN bonds and C=O bonds.
[0058] Figure 5 The XPS spectrum of the core level region of O1s in the prepared graphitized nanocarbon material is shown in Figure 2. Figure 5There are three peaks at 530.9 eV, 532.6 eV and 533.3 eV, respectively, indicating the existence of C=O, C-OH and O=CO.
[0059] Figure 6 The XPS spectrum of the core energy level region of N1s in the prepared graphitized nanocarbon material is shown in Figure 2. Figure 6 There are three peaks at 398.4 eV, 399.9 eV and 401.4 eV, respectively, indicating pyridinic nitrogen and pyrrolic nitrogen graphitized nitrogen.
[0060] Figure 7 Isotherm adsorption curve of graphitized nanocarbon material prepared from Figure 7 It can be seen that the adsorption curve is type IV and has an obvious HII hysteresis loop, indicating that the material has a mesoporous structure.
[0061] Figure 8 The pore size distribution curve of the prepared graphitized nanocarbon material shows two obvious peaks at around 2 nm and 5 nm, indicating that the material has pores of two different sizes.
[0062] Application Example 1
[0063] The graphitized nanocarbon material prepared in Example 1 was mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 85:10:5, and then mixed with N-methyl-2-pyrrolidone to form a slurry and coated on an area of 1×1 cm 2 The nickel foam substrate coated with the slurry was dried at 60 °C for 24 hours and placed on a tablet press to be pressed at a pressure of 10 MPa to form a graphitized nano-carbon material / nickel foam supercapacitor electrode.
[0064] Test Example 1
[0065] The graphitized nanocarbon material / nickel foam supercapacitor electrode prepared in Application Example 1 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire was used as the counter electrode. The three electrodes were placed in a 6 mol L -1 The electrochemical performance tests such as cyclic voltammetry, constant current charge and discharge, electrode cycle stability and AC impedance were carried out in KOH solution.
[0066] Fig. 9 The graphitized nanocarbon material / nickel foam supercapacitor electrode in Application Example 1 was used as the working electrode. The scanning rate was 10 mV s in the electrochemical window of -1.0 to 0 V. -1 , 20 mV s -1 , 30 mV s -1 10 50 mV s -1 , 10 mVs -1 and 100 mV s-1 The cyclic voltammetry curves at Figure 8 It can be concluded that the graphitized nano-carbon material / nickel foam supercapacitor electrode prepared in Application Example 1 has a rectangular shape on the cyclic voltammetry curves at different scan rates, and the peak area increases with the increase of the scan rate.
[0067] Fig.10 The graphitized nanocarbon material / nickel foam supercapacitor electrode in Application Example 1 is used as the working electrode with a current density of 1.0 A g in the electrochemical window of -1 to 0 V. -1 The constant current charge and discharge curve at Fig.10 It can be concluded that the linear constant current discharge curve of the graphitized nano-carbon material / nickel foam supercapacitor electrode prepared in Application Example 1 reflects the double-layer capacitance performance of the material. The graphitized nano-carbon material-modified nickel foam electrode provided by the present invention has a high capacitance at 1 A g -1 The specific capacitance at the current density is 448 F g -1 .
[0068] Fig.11 The AC impedance test result of the graphitized nano-carbon material / nickel foam supercapacitor electrode as the working electrode in Application Example 1 is shown in FIG. Fig.11 It can be concluded that the graphitized nanocarbon material / nickel foam supercapacitor electrode prepared in Application Example 1 has a -2 ~10 5 The straight line of the Nyquist curve in the frequency range of HZ is almost perpendicular to the horizontal axis in the low-frequency region, showing good material transmission ability. The intersection value of the curve and the real part Z' is 0.17 Ω, proving that the ohmic internal resistance of the prepared electrode material is small.
[0069] Fig.12 The graph is a graph showing the electrode stability performance test results of the graphitized nanocarbon material / nickel foam supercapacitor electrode as the working electrode in Application Example 1. Fig.11 It can be concluded that the graphitized nanocarbon material / nickel foam supercapacitor electrode prepared in Application Example 1 has a current density of 1 A g -1 The capacitance retention rate after 5000 cycles at a current density of is 98.46%, with high stability.
[0070] Example 2
[0071] First, the fish scales were decomposed to extract the hydrolyzate. The specific steps are as follows. First, the fish scales were decomposed with 36% concentrated hydrochloric acid and 10 molL -1Soak in NaOH for 24 h respectively, then wash with water until neutral and drain naturally. Then accurately weigh 12.5 g of pretreated fish scales and add 250 ml of alkaline protease solution. Stir the above mixture at 75 °C for 12 h until the fish scales are completely decomposed, and then filter with filter membranes with pore sizes of 0.45 μm and 0.22 μm in turn. The filtrate is heated and stirred at 75 °C for 4 h to obtain a uniformly concentrated carbon precursor solution. Take 30 ml of the precursor solution, add 0.02 mol ferric chloride to it, and stir for 1 hour to form an orange transparent solution; transfer this solution to a corundum boat and dry it at 80 °C to obtain a green solid substance, which is then placed in a tube furnace and heated to 1000 °C at a heating rate of 5 °C / min for carbonization for 3 hours to obtain a black solid substance. After grinding, this black solid substance is soaked in an appropriate amount of concentrated hydrochloric acid for 12 h, then washed with ethanol and water until neutral, centrifuged, and dried at 80 °C to obtain a graphitized nanocarbon material.
[0072] Application Example 2
[0073] The graphitized nanocarbon material prepared in Example 2 was mixed with acetylene black and polytetrafluoroethylene in a mass ratio of 85:10:5, and then mixed with N-methyl-2-pyrrolidone to form a slurry and coated on an area of 1×1 cm 2 The nickel foam substrate coated with the slurry was dried at 60 °C for 24 hours and placed on a tablet press to be pressed at a pressure of 10 MPa to form a graphitized nano-carbon material / nickel foam supercapacitor electrode.
[0074] Test Example 2
[0075] The graphitized nanocarbon material / nickel foam supercapacitor electrode prepared in Application Example 2 was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the platinum wire was used as the counter electrode. The three electrodes were placed in a 6 mol L -1 The electrochemical performance tests such as cyclic voltammetry, constant current charge and discharge, electrode cycle stability and AC impedance were carried out in KOH solution.
[0076] Fig.13 The graphitized nanocarbon material / nickel foam supercapacitor electrode in Application Example 2 was used as the working electrode. The scanning rate was 10 mV s in the electrochemical window of -1.0 to 0 V. -1 , 20 mV s -1 , 30 mV s -1 10 50 mV s -1 , 10 mVs -1 and 100 mV s -1 The cyclic voltammetry curves at Fig.12It can be concluded that the graphitized nanocarbon material / nickel foam supercapacitor electrode prepared in Application Example 1 has a rectangular shape on the cyclic voltammetry curves at different scan rates, and the peak area increases with the increase of the scan rate.
[0077] Fig.14 The graphitized nanocarbon material / nickel foam supercapacitor electrode in Application Example 2 was used as the working electrode with a current density of 1.0 A g in the electrochemical window of -1.0 ~ 0 V. -1 The constant current charge and discharge curve at Fig.14 It can be concluded that the graphitized nano-carbon material / nickel foam supercapacitor electrode prepared in Application Example 2 presents an approximately linear constant current discharge curve, which reflects the double-layer capacitance performance of the material. The graphitized nano-carbon material modified nickel foam electrode provided by the present invention has a 1.0 Ag -1 The specific capacitance at the current density is 387 F g -1 .
[0078] Fig.15 The graph is a graph showing the AC impedance test result of the graphitized nano-carbon material / nickel foam supercapacitor electrode as the working electrode in Application Example 2. Fig.15 It can be concluded that the graphitized nanocarbon material / nickel foam supercapacitor electrode prepared in Application Example 2 has a high conductivity at 10- 2 ~10 5 The straight line slope of the Nyquist curve in the frequency range of HZ is small in the low-frequency region because the porous structure is very conducive to the transmission of the electrolyte. The intersection value of the curve and the real part Z' is 0.11 Ω, which proves that the ohmic internal resistance of the prepared electrode material is small.
[0079] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A two-dimensional graphitized nanocarbon material, characterized in that: The preparation method is as follows: (1) soaking the biomass fish scales in strong acid and strong alkali solutions in turn, then washing with ultrapure water, draining the water, adding a quantitative biological enzyme and ultrapure water, stirring at 50-80°C for 24 hours, and filtering to obtain a liquid solution; the biological enzyme is an alkaline protease solution; (2) mixing the liquid solution prepared in step (1) with a certain amount of metal catalyst at 40-50°C, stirring evenly, and then vacuum drying for 2-24 hours to obtain a solid substance; the metal catalyst used includes: potassium ferrocyanide, potassium ferrocyanide, ferric chloride, ferric nitrate or ferric sulfate; (3) heating to 800-1000°C at a rate of 4-12°C / min, and drying at a gas flow rate of 80-120 mL·min -1 Under the following conditions, the solid material obtained in step (2) is carbonized for 2 to 8 h; (4) the product obtained in step (3) is treated with acid to remove the metal material therein to obtain a black solid; (5) the product obtained in step (4) is chemically activated with alkali to obtain a two-dimensional graphitized nanocarbon material.
2. The two-dimensional graphitized nanocarbon material according to claim 1, characterized in that: The strong acid solution used in step (1) is concentrated HCl with a mass concentration of 10-40%, and the strong base solution is NaOH solution with a concentration of 1-20 mol·L -1 ; The mass volume ratio of the wet weight of fish scales and HCl solution or NaOH solution is (40~50) g: (240~300) mL.
3. The two-dimensional graphitized nanocarbon material according to claim 1 or 2, characterized in that: The gas used in step (3) is nitrogen, argon or a mixture of the two.
4. The two-dimensional graphitized nanocarbon material according to claim 1 or 2, characterized in that: The acid used in step (4) includes concentrated hydrochloric acid, concentrated sulfuric acid or concentrated nitric acid.
5. The two-dimensional graphitized nanocarbon material according to claim 1 or 2, characterized in that: The chemical alkali activation treatment performed in step (5) is as follows: KOH or NaOH is added to the black substance prepared in step (4), with the mass ratio of the black substance to the alkali being 1:(5-10), and the mixture is refluxed at 80°C-130°C for 3-6 hours, and then the solvent is evaporated to dryness. The obtained solid is heated to 800°C at a rate of 5-20°C / min, and treated for 2 hours at a gas flow rate of 80-120 ml / min.
6. The two-dimensional graphitized nanocarbon material according to claim 1, characterized in that: The specific surface area of the two-dimensional graphitized nanocarbon material is 900 to 1300 m 2 ·g -1 .
7. The use of the two-dimensional graphitized nanocarbon material in electrode materials according to any one of claims 1 to 6, characterized in that: The following steps are also included: (6) Mix the material obtained in step (5) with a certain amount of binder and conductive agent to form a slurry, and apply it on the processed surface of 1×1 cm 2 (7) constructing a three-electrode system and performing electrochemical tests on the electrode obtained in step (6).
8. The use of the two-dimensional graphitized nanocarbon material in electrode materials according to claim 7, characterized in that: The mass ratio of the materials used is two-dimensional graphitized nanocarbon material: binder: conductive agent = (70-90): (5-15): (5-20), the binder is polyvinylidene fluoride or polytetrafluoroethylene, and the conductive agent is acetylene black or Super-p.
9. The use of the two-dimensional graphitized nanocarbon material in electrode materials according to claim 7 or 8, characterized in that: The electrolyte solution is 6.0 mol·L -1 KOH solution.
Citation Information
Patent Citations
Multi-atom co-doped porous carbon nanosheet electrode material and preparation method and application thereof
CN107331525A
Method for preparing classification porous carbon materials from fish scales
CN109354004A
